Phenotypical characterization of Candida spp. isolated from crop of parrots (Amazona spp.) - Vieira, Renata G. [UNESP]; Acqua Coutinho, Selene D. [UNESP] (Revista Pesquisa Veterinaria Brasileira, 2009)
Renata G. Vieira R.G. & Acqua Coutinho S.D. 2009. Phenotypical characterization of Candida spp. isolated from crop of parrots (Amazona spp.). Pesquisa Veterinaria Brasileira 29(6):452-456. Curso de Pos-Graduagdo em Imunopatologia Veterinaria, Universidade Paulista, Rua Agariba 48, São Paulo, SP 05053010, Brazil. E-mail: selene@uol.com.brThe purpose of this study was to characterize Candida isolates from crop of parrots. Forty baby parrots of genus Amazona, species aestiva and amazonica that were apprehended from wild animal traffic were used: 18 presented ingluvitis and 22 other alterations, but showing general debilitation. Samples were seeded on Sabouraud dextrose agar with chloramphenicol after be obtained by the introduction of urethral probe through the esophagus. Based on morphology and biochemical reactions (API 20C) Candida was confirmed; it was still searched the production of proteinase and phospholipase, virulence factors for Candida species. Candida spp. were isolated from 57.5% parrots, being 72.2% from birds with ingluvitis and 45.5% from without ones. Twenty-five strains of Candida were isolated, 60% and 40%, respectively from parrots with and without ingluvitis, and were speciated: 28% C. humicola, 24% C. parapsilosis, 20% C. guilliermondii, 20% C. famata, and 8% C. albicans. These results demonstrate that C. albicans is not the most frequent species isolated, and it is the first report that shows C. guilliermondii, C. famata, and C. humicola causing infection in parrots. Many isolates presented filamentation (76%), 100% produced proteinase and 68% phospholipase. The observation of Candida spp. producing virulence factors reinforce the pathogenic role of these yeasts in the cases studied.
Caracterização fenotípica de Candida spp. isoladas de inglúvio de papagaios (Amazona spp.)
Keywords: Candida spp.; candidiasis; crop; ingluvitis; parrots; Amazona spp.